An Analysis of Writing Collocation Used By The Ninth Grade of SMPN 3 Madiun - Theresia Budi Sucihati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
The purpose of this study was to investigate collocation in the classroom. Junior high schools were used for research purposes. The goals of this study were to (1) discover different types of collocation in students' writing. (2) Described the meaning of a collocation found in student writing. The research method used was qualitative. The subject was junior high school ninth grade, and the participants were 32 students from 9F. The data gathered served as a record for the students. There were 125 lexical collocations and 60 grammatical collocations discovered. Except for The GE7, all types of collocation were discovered. Furthermore, there are 10 conceptual meanings, 5 connotative meanings, 4 social meanings, 10 total meanings affective meanings, 1 reflected meaning, 24 collocative meanings, and 6 thematic meanings used in students' writing.